Pengembangan Nanoemulsi Ekstrak Daun Kelor (Moringa Oleifera) Sebagai Antioksidan, Antibakteri Dan Antiluka - Hidayat, Muh Akbar; Hartati, Hartati; Pagarra, Halifah; Sahribulan, Sahribulan (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
This study aims to determine the effect of moringa leaf extract nanoemulsion (Moringa Oleifera Lamk.) on bacterial growth, antioxidant activity and wound healing potential in white rats (Rattus novegicus). The research method includes extraction of Moringa, making nanoemulsion of Moringa leaf extract concentrations of 75, 100 and 125 milligrams. Droplet nanoemulsion using Particle Size Analyzer (PSA), antibacterial with inhibition zone diameter (mm), antioxidant with DPPH (1,1 diphenyl-2-picrylhydrazyl) and measurement of wound healing activity by determining the percentage of wound closure in rats. The study used a completely randomized design (CRD) and Analysis of Variant (ANOVA) test followed by Tukey test. Antioxidant activity obtained IC50 Formula 1 amounted to 157.35 ppm, Formula 2 amounted to 123.40 ppm, Formula 3 amounted to 110.12 ppm, Moringa leaves extract amounted to 58.63 ppm and BHA comparison amounted to 6.84 ppm. Moringa leaf extract and nanoemulsion formula showed good wound healing activity which was faster than the positive control. It is found that moringa leaf extract and nanoemulsion formulation have antibacterial activity against S. aureus and E. coli. The wound healing activity of the nanoemulsion formulation was classified as good in mice with a faster wound healing process than the positive control.